K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 11 2017

a3+b3=\(\)\(\left(\left(\frac{-1+\sqrt{2}}{2}\right)^2-\left(\frac{-1+\sqrt{2}}{2}\right)\left(\frac{-1-\sqrt{2}}{2}\right)+\left(\frac{-1-\sqrt{2}}{2}\right)^2\right)\)\(\left(\frac{-1+\sqrt{2}}{2}+\frac{-1-\sqrt{2}}{2}\right)\)=\(-\left(\frac{-1-2\sqrt{2}+2}{4}+\frac{-1+2\sqrt{2}+2}{4}+\frac{1}{4}\right)\)

=\(-\left(\frac{1-2\sqrt{2}+2+1+2\sqrt{2}+2+1}{4}\right)\)=\(\frac{-7}{4}\)

10 tháng 11 2017

Kết quả là \(-\frac{7}{4}\)

11 tháng 11 2017

Ta có:

\(\frac{a+1}{1+b^2}=a+1-\frac{\left(a+1\right)b^2}{1+b^2}\ge a+1-\frac{\left(a+1\right)b^2}{2b}=a+1-\frac{ab+b}{2}\left(1\right)\)

Tương tụ ta có:

\(\hept{\begin{cases}\frac{\left(b+1\right)}{1+c^2}\ge b+1-\frac{bc+c}{2}\left(2\right)\\\frac{\left(c+1\right)}{1+a^2}\ge c+1-\frac{ca+a}{2}\left(3\right)\end{cases}}\)

Từ (1), (2), (3) ta có:

\(M\ge a+b+c+3-\frac{ab+bc+ca+a+b+c}{2}\)

\(=3+3-\frac{ab+bc+ca+3}{2}\)

\(\ge\frac{9}{2}-\frac{\left(a+b+c\right)^2}{6}=3\)